2021
DOI: 10.1039/d0dt03962d
|View full text |Cite
|
Sign up to set email alerts
|

Copper(ii) complexes with tridentate halogen-substituted Schiff base ligands: synthesis, crystal structures and investigating the effect of halogenation, leaving groups and ligand flexibility on antiproliferative activities

Abstract: To investigate the effect of different halogen substituents, leaving groups and the flexibility of ligand on the anticancer activity of copper complexes, sixteen copper(II) complexes with eight different tridentate Schiff-base...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Apart from this, the Cu-N py bond distance of complexes L 1 CuCl-L 4 CuCl falls within the range of the reported data for the copper(II) complexes containing a pyridyl ligand. [47][48][49][50][51] Intrigued by the difference in the molecular structures of the copper(II) complexes L 1 CuCl-L 4 CuCl due to the length of the pyridyl arm, we aim to investigate the difference in the binding modes and reactivity pattern of the nitrite anion bound to the L 1 Cu + and L 2 Cu + fragments. However, only L 1 Cu (O 2 N) crystallizes in the monoclinic space group P21/c and has a mononuclear structure as shown in Fig.…”
Section: Papermentioning
confidence: 99%
“…Apart from this, the Cu-N py bond distance of complexes L 1 CuCl-L 4 CuCl falls within the range of the reported data for the copper(II) complexes containing a pyridyl ligand. [47][48][49][50][51] Intrigued by the difference in the molecular structures of the copper(II) complexes L 1 CuCl-L 4 CuCl due to the length of the pyridyl arm, we aim to investigate the difference in the binding modes and reactivity pattern of the nitrite anion bound to the L 1 Cu + and L 2 Cu + fragments. However, only L 1 Cu (O 2 N) crystallizes in the monoclinic space group P21/c and has a mononuclear structure as shown in Fig.…”
Section: Papermentioning
confidence: 99%
“…On the other hand, transition-metal complexes are being used in pharmaceutical and medicinal chemistry since the discovery of cisplatin . Several coordination compounds of metal ions (chromium, cobalt, copper, manganese, molybdenum, palladium, ruthenium, tungsten, vanadium, and zinc) have been applied in the treatment of various diseases owing to their antimicrobial and antioxidant, anticancer, , antiproliferative, , anti-inflammatory, DNA binding and cytotoxicity, ,,, antitumor, and antidiabetic activities. Studies also indicated that Zn­(II) complexes exhibit anti-inflammatory, antidiabetic, antioxidant, and antimicrobial activities, , whereas Cu­(II) complexes exhibited promising antimicrobial, antioxidant, antiviral, DNA binding, ,, and antiproliferative activities.…”
Section: Introductionmentioning
confidence: 99%
“…Several coordination compounds of metal ions (chromium, cobalt, copper, manganese, molybdenum, palladium, ruthenium, tungsten, vanadium, and zinc) have been applied in the treatment of various diseases owing to their antimicrobial and antioxidant, anticancer, , antiproliferative, , anti-inflammatory, DNA binding and cytotoxicity, ,,, antitumor, and antidiabetic activities. Studies also indicated that Zn­(II) complexes exhibit anti-inflammatory, antidiabetic, antioxidant, and antimicrobial activities, , whereas Cu­(II) complexes exhibited promising antimicrobial, antioxidant, antiviral, DNA binding, ,, and antiproliferative activities. Previous studies of a zinc­(II) complex of quinoline derivative ligand indicated an in vitro biological screening effect tested against four bacterial strains, Escherichia coli and Pseudomonas aeruginosa (Gram-negative) as well as Staphylococcus aureus and Bacillus subtilis (Gram-positive).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, copper-containing complexes or materials also behave as bearers of high thermal and electrical conductivity, or catalytic and sensory features. As examples, the following papers could be mentioned to show the current strives on the design of copper(II) complexes showing some of the above mentioned properties, mainly the antiproliferative one [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. To date, one of the most intensively studied groups of copper(II) complexes in terms of their possible clinical use as anticancer agents is the copper(II) complexes called Casiopeínas ® , whose composition can be expressed by the formulas [Cu( N – N )( N – O )] + and/or [Cu( N – N )( O – O )] + , where ( N – N ) represents an aromatic heterocyclic diimine, such as 2,2′-bipyridine (bpy) or 1,10-phenanthroline (phen), ( N – O ) and ( O – O ) stands for an amino acid, and acetylacetone, respectively [ 11 ].…”
Section: Introductionmentioning
confidence: 99%